Oak persistence in Mediterranean landscapes: the combined role of management, topography, and wildfires - Acácio, Vanda; Holmgren, Milena (Ecology and society, 2010)
Mediterranean ecosystems have been shaped by a history of human and ecological disturbances. Understanding the dynamics of these social-ecological systems requires an understanding of how human and ecological factors interact. In this study, we assess the combined role of management practices and biophysical variables, i.e., wildfire and topography, to explain patterns of tree persistence in a cork oak (Quercus suber L.) landscape of southern Portugal. We used face-to-face interviews with landowners to identify the management practices and the incentives that motivated them. We used aerial photographs and a Geographic Information System (GIS) to classify vegetation patch-type transitions over a period of 45 years (1958-2002) and logistic regression to explain such changes based on management and biophysical factors. The best model explaining vegetation transitions leading to cork oak persistence in the landscape included both biophysical and management variables. Tree persistence was more likely to occur on steeper slopes, in the absence of wildfires, and in the absence of understory management. We identified ecological, ideological, and economical barriers that preclude oak persistence and that are important to consider in implementing efficient environmental policies for adequate conservation and reforestation programs of Mediterranean cork oak landscapes.
Keywords: agroforestry system; alternative ecosystem state; Cistus ladanifer; Land degradation; Mediterranean; Portugal; Quercus suber; Shrub encroachment; succession; vegetation transition